Does revenue diversification strategy affect the financial sustainability of Malaysian Public Universities? a panel data analysis - Abdullah Jaafar, Johanna; Abdul Latiff, Ahmed Razman; Mat Daud, Zaidi; Osman, Mohammad Noor Hisham (Palgrave Macmillan, 2023)
Financial sustainability had become a primary concern among public universities worldwide due to the declining trend of government's funding and the unceasing growth in higher education cost. Hence, public universities are forced to generate alternative income sources. Resource dependency theory asserts that revenue diversification is a prudent strategy for non-profit organisations to mitigate their financial challenges. However, studies that focused on revenue diversification strategy's potential among public universities are yet to be proven. Thus, this study examined the effect of revenue diversification on the financial sustainability of 20 Malaysian public universities using a panel data approach. Revenue diversification is measured using the Hirschman Herfindahl Index, while financial sustainability was proxied by the Return on Assets (ROA) and Net Profit Margin. The result discovered that revenue diversification had a significant positive relationship with financial sustainability when ROA is used as a proxy. This study contributes to resource dependency theory, whereby the revenue diversification effect was tested and found to be significant in the context of public universities. It also highlighted the importance of revenue diversification to overcome the financial sustainability issue, which became a primary concern of Malaysian public universities in recent years.